What Causes Racial Health Care Disparities? A Mixed-Methods Study Reveals Variability in How Health Care Providers Perceive Causal Attributions. (17th March 2018) - Gollust, Sarah E.; Cunningham, Brooke A.; Bokhour, Barbara G.; Gordon, Howard S.; Pope, Charlene; Saha, Somnath S.; Jones, Dina M.; Do, Tam; Burgess, Diana J.
Progress to address health care equity requires health care providers' commitment, but their engagement may depend on their perceptions of the factors contributing to inequity. To understand providers' perceptions of causes of racial health care disparities, a short survey was delivered to health care providers who work at 3 Veterans Health Administration sites, followed by qualitative interviews (N = 53). Survey data indicated that providers attributed the causes of disparities to social and economic conditions more than to patients' or providers' behaviors. Qualitative analysis revealed differences in the meaning that participants ascribed to these causal factors. Participants who believed providers contribute to disparities discussed race and racism more readily, identified the mechanisms through which disparities emerge, and contextualized patient-level factors more than those who believed providers contributed less to disparities. Differences in provider understanding of the underlying causal factors suggest a multidimensional approach to engage providers in health equity efforts.